A study of cultural heritage and lunar new year cuisine: Preserving the sustainability of the Chinese community - Fauziah, Miftahul; Ratnaningsih, Nani; Marwanti, Marwanti (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
Indonesians of Chinese descent, scattered across various regions, continue to contribute to the development of the Chinese community while enriching Indonesia’s cultural diversity. In a multicultural society, one of the main challenges faced is the process of acculturation, particularly amid the influence of modernity. This article discusses efforts to preserve the continuity of Chinese community traditions in Indonesia by highlighting the role of Lunar New Year cuisine as a form of cultural expression. Modernity and the acculturation of local cultures have led to variations in Lunar New Year culinary practices across different Chinese communities. This study aims to examine Chinese cuisine as an indicator of the continuity of traditions and community identity. The research method employed is qualitative, utilizing secondary data analysis through a literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The findings indicate that Chinese community traditions have not declined but have instead transformed and blended with local culture. This is reflected in Lunar New Year celebrations in Indonesia, such as the Grebeg Sudiro festival, as well as ritual practices and traditional food offerings. Foods such as kue mangkok, kue keranjang (nian gao), and agar-agar hold symbolic meanings related to hopes for prosperity, happiness, and good fortune. Thus, the Lunar New Year celebration serves not only as a religious tradition but also as a means of cultural preservation and the strengthening of the multicultural identity of Indonesian society.   Warga Indonesia keturunan Tionghoa yang tersebar di berbagai daerah terus berkontribusi terhadap perkembangan komunitas Tionghoa sekaligus memperkaya keragaman budaya Indonesia. Dalam masyarakat multikultural, salah satu tantangan utama yang dihadapi adalah proses akulturasi, terutama di tengah pengaruh modernitas. Artikel ini membahas upaya menjaga keberlanjutan tradisi komunitas Tionghoa di Indonesia dengan menyoroti peran kuliner Imlek sebagai bentuk ekspresi budaya. Modernitas dan akulturasi budaya lokal menyebabkan variasi dalam praktik kuliner Imlek di berbagai komunitas Tionghoa. Penelitian ini bertujuan mengkaji kuliner Tionghoa sebagai penanda keberlanjutan tradisi dan identitas komunitas. Metode penelitian yang digunakan adalah kualitatif dengan analisis data sekunder melalui studi literatur menggunakan pendekatan Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Hasil kajian menunjukkan bahwa tradisi komunitas Tionghoa tidak mengalami kemunduran, melainkan bertransformasi dan melebur dengan budaya lokal. Hal ini tercermin dalam perayaan Imlek di Indonesia, seperti festival Grebeg Sudiro serta praktik ritual dan sajian makanan khas. Makanan seperti kue mangkok, kue keranjang (nian gao), dan agar-agar memiliki makna simbolis terkait harapan akan rezeki, kebahagiaan, dan keberuntungan. Dengan demikian, perayaan Imlek tidak hanya berfungsi sebagai tradisi keagamaan, tetapi juga sebagai sarana pelestarian budaya dan penguatan identitas multikultural masyarakat Indonesia.